Investigating longitudinal changes to frontal cortico-striatal tracts in Huntington’s disease: the IMAGE-HD study - Brendan Tan; Rosita Shishegar; Stuart Oldham; Alex Fornito; Govinda Poudel; Nellie Georgiou-Karistianis (Brain Imaging and Behavior, 2022)
The striatum is the principal site of disease pathology in Huntington’s disease and contains neural connections to numerous cortical brain regions. Studies examining abnormalities to neural connections find that white matter integrity is compromised in HD; however, further regional, and longitudinal investigation is required. This paper is the first longitudinal investigation into region-based white-matter integrity changes in Huntington’s Disease. The aim of this study was to better understand how disease progression impacts white matter tracts connecting the striatum to the prefrontal and motor cortical regions in HD. We used existing neuroimaging data from IMAGE-HD, comprised of 25 pre-symptomatic, 27 symptomatic, and 25 healthy controls at three separate time points (baseline, 18-months, 30-months). Fractional anisotropy, axial diffusivity and radial diffusivity were derived as measures of white matter microstructure. The anatomical regions of interest were identified using the Desikan-Killiany brain atlas. A Group by Time repeated measures ANCOVA was conducted for each tract of interest and for each measure. We found significantly lower fractional anisotropy and significantly higher radial diffusivity in the symptomatic group, compared to both the pre-symptomatic group and controls (the latter two groups did not differ from each other), in the rostral middle frontal and superior frontal tracts; as well as significantly higher axial diffusivity in the rostral middle tracts only. We did not find a Group by Time interaction for any of the white matter integrity measures. These findings demonstrate that whilst the microstructure of white matter tracts, extending from the striatum to these regions of interest, are compromised during the symptomatic stages of Huntington’s disease, 36-month follow-up did not show progressive changes in these measures. Additionally, no correlations were found between clinical measures and tractography changes, indicating further investigations into the relationship between tractography changes and clinical symptoms in Huntington’s disease are required.

Associations of cardiorespiratory fitness and exercise with brain white matter in healthy adults: A systematic review and meta-analysis - Suzan Maleki; Joshua Hendrikse; Yann Chye; Karen Caeyenberghs; James P. Coxon; Stuart Oldham; Chao Suo; Murat Yücel (Brain Imaging and Behavior, 2022)
Magnetic resonance imaging (MRI) studies have revealed positive associations between brain structure and physical activity, cardiorespiratory fitness, and exercise (referred to here as PACE). While a considerable body of research has investigated the effects of PACE on grey matter, much less is known about effects on white matter (WM). Hence, we conducted a systematic review of peer-reviewed literature published prior to 5 th July 2021 using online databases (PubMed and Scopus) and PRISMA guidelines to synthesise what is currently known about the relationship between PACE and WM in healthy adults. A total of 60 studies met inclusion criteria and were included in the review. Heterogeneity across studies was calculated using Qochran’s q test, and publication bias was assessed for each meta-analysis using Begg and Mazumdar rank correlation test. A meta-regression was also conducted to explore factors contributing to any observed heterogeneity. Overall, we observed evidence of positive associations between PACE and global WM volume (effect size (Hedges’s g) = 0.137, p < 0.001), global WM anomalies (effect size = 0.182, p < 0.001), and local microstructure integrity (i.e., corpus callosum: effect size = 0.345, p < 0.001, and anterior limb of internal capsule: effect size = 0.198, p < 0.001). These findings suggest that higher levels of PACE are associated with improved global WM volume and local integrity. We appraise the quality of evidence, and discuss the implications of these findings for the preservation of WM across the lifespan. We conclude by providing recommendations for future research in order to advance our understanding of the specific PACE parameters and neurobiological mechanisms underlying these effects.